Research into all vanadium redox flow battery energy storage system - Nayar Ruchika (2016)
In the present age, there is an increasing shift in energy generation from conventional sources to the renewable energy sources. This introduces new challenges for the electricity grid. The energy storage systems (ESS) play a pivotal role in this scenario in increasing the reliability of the supply. These are essential for the incorporation of renewable energy sources into the grid and also critical for the development of future smart grids. The energy storage systems have the potential to contribute towards energy efficiency improvement by peak shaving and load levelling, power smoothing and stabilization of the grid for the power generated from the renewable sources. The All Vanadium Redox Flow Battery (VRB) ESS is a promising and up and coming technology for the large scale energy storage applications. It has good performance, high energy efficiency, long life cycle, swift response and low maintenance needs. Therefore, there is a considerable need to get detailed data on the operational characteristics and behaviour of the VRB in order to extract the best possible output and efficiency from this Energy storage system. The purpose of this project is to implement an electrical model of the VRB in Simulink environment based on the physical and mathematical properties of the battery. The model is validated with the results published in [l].It is then executed for a full charge discharge cycle of the VRB. The simulations are run for a constant current (CC) cycle and the operational characteristics of the VRB are analyzed. The model is further used for the sensitivity analysis of the VRB parameters and losses with the variations in the charge/ discharge current for different limits of the state of charge (SOC). The optimum range of operating currents for maximum charge and discharge efficiencies is thus found. Also, it is concluded that the efficiency increases with the increase in the SOC limit.